2016
DOI: 10.1111/cas.13070
|View full text |Cite
|
Sign up to set email alerts
|

Intensity‐specific effect of physical activity on urinary levels of 8‐hydroxydeoxyguanosine in middle‐aged Japanese

Abstract: Physical activity (PA) is recommended to both promote and maintain health and prevent cancer by improving the body's DNA repair system, which is considered a mechanism of cancer prevention. However, associations between PA and urinary levels of 8‐hydroxydeoxyguanosine (8‐OH‐dG), which reflects DNA damage, are unclear. This cross‐sectional study included 2370 men and 4052 women aged 45–74 years enrolled between 2010 and 2012. Habitual PA was assessed by single‐axis accelerometer and urinary 8‐OH‐dG levels by au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 34 publications
0
10
1
Order By: Relevance
“…Moderate physical activity also reduced oxidative stress. (37,38) At the same time, GSH (Glutathione-SH), catalase, glutathione peroxidase activity, (2,39) and total antioxidant capacity (38) were increased. The salivary 8-OHGua levels were significantly lower in persons who performed moderate physical activity.…”
Section: Discussionmentioning
confidence: 96%
“…Moderate physical activity also reduced oxidative stress. (37,38) At the same time, GSH (Glutathione-SH), catalase, glutathione peroxidase activity, (2,39) and total antioxidant capacity (38) were increased. The salivary 8-OHGua levels were significantly lower in persons who performed moderate physical activity.…”
Section: Discussionmentioning
confidence: 96%
“…In a study of male Japanese workers, total physical activity—including commuting, working, and sports—was inversely associated with urinary 8-OH-dG levels, independent of other lifestyle factors [17]; furthermore, moderate leisure-time exercise (less than 5 hours per week) was associated with lower concentrations of urinary 8-OH-dG [16]. In a substudy of the Japan Multi-institutional Collaborative Cohort Study, which assessed daily physical activity by using an accelerometer, showed that light-to-vigorous physical activity in women and moderate-to-vigorous physical activity in men were inversely associated with the concentration of urinary 8-OH-dG [15]. In an intervention study among patients with type 2 diabetes, aerobic exercise greatly reduced urinary 8-OH-dG levels [30].…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiological studies have examined the association between physical activity and 8-OH-dG levels, but their results have been inconsistent; some reported an inverse association between physical activity and 8-OH-dG [1517], while others found no obvious association [1820]. To the best of our knowledge, only one study examined the association between total physical activity and m 7 Gua, but failed to detect any significant associations [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, physical activity has been shown to reduce inflammation and oxidative stress in both the general population and patients with CKD 11 . We previously reported the presence of an inverse correlation between daily physical activity and levels of circulating inflammatory cytokines including interleukins 40 and urine 8-hydroxydeoxyguanosine, as an index of whole-body oxidative stress 41 . Further, while prolonged SB markedly reduces micro-and macrovascular dilator function 42 , these impairments can be improved with walking 43 .…”
Section: A C C E P T E D V E R S I O Nmentioning
confidence: 99%